Activities of the Lithuanian Mathematical Society in 1998–2001 - Kubilius, Jonas (Lietuvos matematikos rinkinys, 2001)
The article gives a survey of activities of the Society during last three years. Some problems of the mathematical life in Lithuania are rised.